2021
DOI: 10.1148/radiol.2021204723
|View full text |Cite
|
Sign up to set email alerts
|

Can Preoperative Mapping with Functional MRI Reduce Morbidity in Brain Tumor Resection? A Systematic Review and Meta-Analysis of 68 Observational Studies

Abstract: F unctional MRI (fMRI) is increasingly implemented as a practical preoperative planning tool for brain tumor resection, but a considerable discrepancy between its current use and presumed utility remains. A recent survey among neurosurgeons found variability in the present use and assumed utility of fMRI for preoperative surgical planning in patients with brain tumors. This variation includes clinical and radiographic indications for ordering fMRI, functional paradigms to test in specific case studies, and cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 74 publications
1
10
0
Order By: Relevance
“…There is strong evidence in the literature that accurate preoperative fMRI planning prior to the resection of brain tumors reduces postsurgical morbidity. 38 With current task-based methods, however, the time it takes to get adequate information can extend the scan time up to an hour. Thus, there is a high degree of significance for the neurosurgeon in obtaining optimal imaging quality while reducing imaging time and cost.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is strong evidence in the literature that accurate preoperative fMRI planning prior to the resection of brain tumors reduces postsurgical morbidity. 38 With current task-based methods, however, the time it takes to get adequate information can extend the scan time up to an hour. Thus, there is a high degree of significance for the neurosurgeon in obtaining optimal imaging quality while reducing imaging time and cost.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis has demonstrated that presurgical planning with T-fMRI improves morbidity and mortality. 38 Multiple studies have demonstrated that RS-fMRI mapping can complement T-fMRI and provide necessary mapping when a patient is unable to cooperate with the study or the task fails for some other reason. 10 The low failure rate of RS-fMRI, the automated localization capability of the 3DCNN, and the need for far less scanner time make the proposed method an attractive choice for the preoperative assessment of tumor patients.…”
Section: Discussionmentioning
confidence: 99%
“… Roux et al (2003) showed that all of the 22 intraoperatively identified positive language sites were correlated to preoperative fMRI. A recent meta-analysis showed that preoperative fMRI decreases postoperative neurological morbidity ( Luna et al, 2021 ), whereas a recent review found that fMRI has shown excellent utility for lateralizing language dominance, superior to the Wada test for many patients ( Qadri et al, 2021 ). It is possible that combining task-based fMRI with cerebrovascular reactivity mapping (CVR) may help overcome some of the issues related to vascular uncoupling in the presence of brain tumors, although the impact of CVR mapping upon the accuracy of fMRI compared with DCS has not been adequately investigated to date.…”
Section: Discussionmentioning
confidence: 99%
“…However, the statistical validity of these results remains in question because of the significant differences in data collection and aggregation between TMS and fMRI, leading to far more data points for TMS despite a similar number of patients. In addition, TMS lacks large, aggregated studies showing its clinical utility for preoperative language mapping ( Luna et al, 2021 ). TMS also lacks comparable evidence to fMRI with respect to lateralizing language dominance ( Qadri et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tb-fMRI is already widely applied for this purpose, as it was found to be reliable in identifying the motor and language networks [3,4]. Moreover, meta-analytic studies and comparisons with direct electrical stimulation (DES), the gold standard in terms of localization of functional areas at the intraoperative level, support that tb-fMRI is a robust tool for presurgical motor planning [5] and may mitigate morbidity and neurological deficits in the postoperative phase [6]. Nevertheless, this technique presents some limitations, mainly associated with the acquisition: it is necessary for the patients to be able and suitable to be trained to perform the task; therefore, they should not present severe neurological deficits or cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%